Antiquités of Mexico : comprising facsimiles of acient mexican paintings and hieroglyphics preserved in the Royal Libraries of Paris, berlim, and Dresden ; in the Imperial Library ; in the Borgian Museum at Rome ; in the Library of the Institut at Bologna and in the Boldeian Library at oxford, together with teh monuments of New Spain - Dupaix, Guillaume. (A. Aglio)
Conteúdo: v. 1-3. Lâminas -- v. 4-9. Texto.